A Review on Ayurvedic Medicinal Herbs as Remedial Perspective for COVID-19 - Gyawali, Rajendra; Paudel, Prem Narayan; Basyal, Dipak; Setzer, William N.; Lamichhane, Saroj; Paudel, Madan Kumar; Gyawali, Shaphal; Khanal, Prajwal (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Recent outbreaks in a new type of coronavirus, novel coronavirus (COVID-19) disease causing respiratory infection have significantly hampered the public health. Traditional herbs provide enormous scope to bring out viable alternatives against viral diseases, considering non-availability of suitable drug for emerging viral diseases. Methods: The methodological activities involved during a literature review were; (1) designing the review concept, (2) conducting the review on review papers, research papers, bulletins, official websites, (3) analysis of previous publications and (4) writing up the review paper. The integrative literature review and paper preparation process was done from our own practical experience and influenced by various guidelines during February 2020 to May 2020.Results: Herbal medicines and their active phytochemicals against some viruses including severe acute respiratory syndrome (SARS), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that causes COVID-19 pandemic, middle east respiratory syndrome coronavirus (MERS-COV), rhinovirus, human herpes virus (HSV-I & II), human immunodeficiency virus (HIV), coxsackievirus (CV), enterovirus 71 (EV71), hepatitis B virus (HBV), hepatitis C virus (HCV), herpes simplex virus, influenza A/H1N1 virus, coronavirus and respiratory syncytial virus (RSV) were extensively reviewed. In view of the possible benefit of herbal medicine for the prevention and control of the viral infectious diseases, Ayurvedic herbs could be useful an alternative and integrated approach to decrease the morbidity and mortality and enhance host immunity against COVID-19 attack.Conclusion: Ayurvedic herbs have enough possibilities to be employed both for the prevention and treatment of COVID-19.